2016
DOI: 10.1155/2016/5623718
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in Adults: The Role of MDCT in the Identification of the Site and Cause of Obstruction

Abstract: Unlike pediatric intussusception, intestinal intussusception is infrequent in adults and it is often secondary to a pathological condition. The growing use of Multi-Detector Computed Tomography (MDCT) in abdominal imaging has increased the number of radiological diagnoses of intussusception, even in transient and nonobstructing cases. MDCT is well suited to delineate the presence of the disease and provides valuable information about several features, such as the site of intussusception, the intestinal segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 23 publications
1
50
0
9
Order By: Relevance
“…Computed tomography is regarded as the most useful imaging technique, with a diagnostic accuracy of 58–100% [7], [9]. CT is not affected by body habitus or the presence of intraluminal gas, both of which commonly limit ultrasonographic diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography is regarded as the most useful imaging technique, with a diagnostic accuracy of 58–100% [7], [9]. CT is not affected by body habitus or the presence of intraluminal gas, both of which commonly limit ultrasonographic diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the abdominal ultrasound, the abdominal helical computed tomography (CT) is a gold standard due to its high specificity and sensitivity for determining the etiology, level and degree of the obstruction [7,8]. The typical imaging of intussus- ception with target-like appearance has an accuracy of 90% [7].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal MDCT has been shown to be the imaging modality of choice for the detection and assessment of adult bowel intussusception, with a reported accuracy of 58-100%. 5 In our case series, a retrospective review of clinical records of five cases of adult intussusception is demonstrated on CT images. The above patients, who presented with acute abdomen, were imaged with CT. Etiological factors included intestinal polyp, intra bowel leiomyoma, jejunal lipoma, lymph nodes, as well as an idiopathic cause.…”
Section: Case Reportmentioning
confidence: 99%